1971
DOI: 10.1139/m71-019
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of rutin by Aspergillus flavus. Purification of the dioxygenase, quercetinase

Abstract: MILLS. 1971. Degradation of rutin by Aspergillr~s pavrts. Purification of the dioxygenase, quercetinase. Can. J. Microbiol. 17: 11 1-1 18. Evidence is presented that a single enzyme, quercetinase, is responsible for the degradation of quercetin by Aspergillus flavlts to yield carbon monoxide and a depside, 2-protocatechuoylphloroglucinol carboxylic acid. A procedure for the isolation of the dioxygenase as a homogeneous protein is described. The most purified preparation degraded 10 800 umoles of quercetin/h mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 2 publications
0
50
1
Order By: Relevance
“…This procedure reduced the residual glycosylation to Ϸ3-5% (wt͞wt). An activity assay, carried out according to the procedure of Oka et al (16), indicated that deglycosylation had no adverse effect on the catalytic efficiency of 2,3QD.…”
Section: Methodsmentioning
confidence: 99%
“…This procedure reduced the residual glycosylation to Ϸ3-5% (wt͞wt). An activity assay, carried out according to the procedure of Oka et al (16), indicated that deglycosylation had no adverse effect on the catalytic efficiency of 2,3QD.…”
Section: Methodsmentioning
confidence: 99%
“…Quercetinases have been isolated from the fungi Aspergillus flavus , 1099 Aspergillus niger , 1110 Aspergillus japonicus , 1111 and Penicillium olsonii 1112 and the prokaryotes Bacillus subtilis 1113,1114 and Streptomyces sp. FLA. 1115 All quercetinase enzymes are glycoproteins with 16–47% sugar content (w/w).…”
Section: Substrate Activation By Cuii Sitesmentioning
confidence: 99%
“…Quercetinase has been reported to contain two Cu II centers per molecule. [19,20] Recent diffraction studies on single crystals of quercetin 2,3-dioxygenase obtained from Aspergillus japonicus, at a resolution of 1.8 Å , showed that the enzyme forms homodimers, which are stabilized by an Nlinked heptasaccharide at the dimer interface. [21] Each unit is mononuclear, with a type 2 copper center displaying two distinct geometries: a distorted tetrahedral coordination with three histidine units and one water molecules, and a distorted trigonal bipyramidal environment with an additional carboxylate.…”
Section: Introductionmentioning
confidence: 99%